Characterization of biochar-derived organic matter extracted with solvents of differing polarity via ultrahigh-resolution mass spectrometry. (November 2022) - Tian, Y.X.; Guo, X.; Ma, J.; Liu, Q.Y.; Li, S.J.; Wu, Y.H.; Zhao, W.H.; Ma, S.Y.; Chen, H.Y.; Guo, F.
Abstract: In recent years, biochar, a porous carbon-based material, has gained attention for its application prospects in contaminated soil remediation and soil improvement. Biochar-derived organic matter has a key role in influencing the migration and transformation of soil elements and pollutants. However, existing research concerning the molecular characteristics of biochar-derived organic matter is limited. Here, we used four polar solvents — dichloromethane (CH2 Cl2 ), acetone (CH3 COCH3 ), methanol (CH3 OH), and distilled water (H2 O) — to extract organic matter from soybean straw biochar and wheat straw biochar by accelerated solvent extraction (ASE). We characterized the extracts using Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). We found considerable differences in organic matter according to the extraction solvents; such differences were related to the polarity of the solvent, as well as intermolecular forces between the solvent and organic matter. CH3 OH extracted the most biochar-extractable organic matter components because CH3 OH can weaken or destroy oxygen bridge bonds in biochar and form hydrogen bonds with small-molecule organic compounds. CH3 OH and H2 O have strong extraction capacity for compounds containing heteroatoms. CH2 Cl2 -extractable organic matter is relatively labile and bioavailable, while CH3 OH- and H2 O-extractable organic matters are relatively stable. In addition, the binding capacity of biochar-derived organic matter for minerals and pollutants differed among fractions, in part because of differences in molecular weight, atomic O/C and H/C ratios, heteroatom distribution, and biomolecular compounds present in biochar-derived organic matter. The findings in this study help to select appropriate extractants to analyze biochar-derived organic matter for various research purposes, and provides a theoretical basis for biochar-based remediation of contaminated soil. Graphical abstract: Image 1 Highlights: FT-ICR-MS was used to reveal characteristics and possible environmental behavior of BEOM at the molecular level. The difference in BEOM was related to the polarity of extractant and intermolecular force between the extractant and organic matter. CH3 OH can extract the most BEOM components, CH3 OH and H2 O have strong extraction capacity for heteroatom compounds. CH2 Cl2 -extractable organic matter is relatively labile and easily biodegraded.